2022
DOI: 10.3390/cancers14040872
|View full text |Cite
|
Sign up to set email alerts
|

The Role of microRNAs in Cancer: Functions, Biomarkers and Therapeutics

Abstract: MicroRNAs (miRs) are small non-coding RNAs acting as post-transcriptional regulators of gene expression with important roles in almost all biological pathways, including development, differentiation, cell cycle, proliferation, and apoptosis [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…miRNAs are a subtype of ncRNAs species which have 20–22 nucleotides. Considering the involvement of several miRNAs in tumor suppression, progression, and cellular pathway modulation, miRNAs regulation might provide promising opportunities in cancer treatment (Peng & Croce, 2016; Tucci, 2022). miRNA plays a role in regulating gene expression by regulating post‐transcriptional and transcriptional steps of target genes.…”
Section: Ncrnas Applications In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are a subtype of ncRNAs species which have 20–22 nucleotides. Considering the involvement of several miRNAs in tumor suppression, progression, and cellular pathway modulation, miRNAs regulation might provide promising opportunities in cancer treatment (Peng & Croce, 2016; Tucci, 2022). miRNA plays a role in regulating gene expression by regulating post‐transcriptional and transcriptional steps of target genes.…”
Section: Ncrnas Applications In Cancer Treatmentmentioning
confidence: 99%
“…In this regard, ncRNAs might be new therapeutic approaches for malignancies (Liu & Wang, 2016;Yousefi et al, 2017). Furthermore, current main cancer treatments such as surgery, chemotherapy, radiotherapy and combination therapy face limitations and obstacles due to the complexity of tumor cell changes and their resistance to current treatments (Gao et al, 2020;Valizadeh et al, 2019;Yousefi et al, 2017). However, new findings showed that ncRNAs can be selected candidates to overcome these challenges (Wang, Han, et al, 2019).…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…Moreover, microRNAs have shown great potential for identifying tissue of origin for cancers of unknown primary origin [21]. microRNAs have been investigated as prognostic and diagnostic biomarkers extensively in the research community, and have even been found to be deregulated in numerous cancers [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microRNAs (miRNAs) have been analysed as potential biomarkers for the early detection of various types of cancer, including EOC 6 , 7 miRNAs were discovered as a new class of evolutionarily conserved small non-coding molecules 8 . They play an important regulatory role in cellular homeostasis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, to improve the survival rate of EOC patients, there is an urgent need to identify new diagnostic and theranostic biomarkers characterized by higher specificity and sensitivity. Recently, microRNAs (miRNAs) have been analysed as potential biomarkers for the early detection of various types of cancer, including EOC 6,7 . miRNAs were discovered as a new class of evolutionarily conserved small non-coding molecules 8 .…”
Section: Introductionmentioning
confidence: 99%